56.3k views
1 vote
Determine whether each set {p1,p2} is a linearly independent set in P3.

1. The polynomials p1 (t) = 1 + t2 and p2(t) = 1 - t2.
2. The polynomials p1 (t) = 2t + t2 and p2(t) = 1 + t.
3. The polynomials p1(t) = 2t - 4t2 and p2(t) = 6t2 - 3t.

1 Answer

3 votes

Answer:

1) The polynomials
p_(1)(t) = 1 +t^(2) and
p_(2)(t) = 1-t^(2) are linearly independient, 2) The polynomials
p_(1)(t) = 2\cdot t +t^(2) and
p_(2)(t) = 1+t are linearly independent, 3) The polynomials
p_(1)(t) = 2\cdot t - 4\cdot t^(2) and
p_(2)(t) = 6\cdot t^(2)-3\cdot t are linearly dependent.

Explanation:

A set is linearly independent if and only if the sum of elements satisfy the following conditions:


\Sigma_(i=0)^(n) \alpha_(i) \cdot u_(i) = 0


\alpha_(0) = \alpha_(1) =...=\alpha_(i) = 0

1) The set of elements form the following sum:


\alpha_(1)\cdot p_(1)(t)+\alpha_(2)\cdot p_(2)(t) = 0


\alpha_(1)\cdot (1+t^(2))+\alpha_(2)\cdot (1-t^(2)) = 0


(\alpha_(1)+\alpha_(2))\cdot (1) +(\alpha_(1)-\alpha_(2))\cdot t^(2) = 0

From definition this system of equations must be satisfied:


\alpha_(1) + \alpha_(2) = 0 Eq. 1


\alpha_(1)-\alpha_(2) = 0 Eq. 2

From Eq. 2:


\alpha_(1) = \alpha_(2)

In Eq. 1:


2\cdot \alpha_(1) =0


\alpha_(1) = 0


\alpha_(2) = 0

The polynomials
p_(1)(t) = 1 +t^(2) and
p_(2)(t) = 1-t^(2) are linearly independient.

2) The set of elements form the following sum:


\alpha_(1)\cdot p_(1)(t)+\alpha_(2)\cdot p_(2)(t) = 0


\alpha_(1)\cdot (2\cdot t+t^(2))+\alpha_(2)\cdot (1+t) = 0


\alpha_(2)\cdot (1) +(2\cdot \alpha_(1)+\alpha_(2))\cdot t +\alpha_1 \cdot t^(2) = 0

From definition this system of equations must be satisfied:


\alpha_(2) = 0


2\cdot \alpha_(1)+\alpha_(2) = 0


\alpha_(1) = 0

The polynomials
p_(1)(t) = 2\cdot t +t^(2) and
p_(2)(t) = 1+t are linearly independent.

3) The set of elements form the following sum:


\alpha_(1)\cdot p_(1)(t)+\alpha_(2)\cdot p_(2)(t) = 0


\alpha_(1)\cdot (2\cdot t-4\cdot t^(2))+\alpha_(2)\cdot (6\cdot t^(2)-3\cdot t) = 0


(2\cdot \alpha_(1)-3\cdot \alpha_(2))\cdot t + (-4\cdot \alpha_(1)+6\cdot \alpha_(2))\cdot t^(2) = 0

From definition this system of equations must be satisfied:


2\cdot \alpha_(1)-3\cdot \alpha_(2) = 0 (Eq. 1)


-4\cdot \alpha_(1)+6\cdot \alpha_(2) =0 (Eq. 2)

It is easy to find that each coefficient is multiple of the other one, that is:


\alpha_(1) =(3)/(2)\cdot \alpha_(2) (From Eq. 1)


\alpha_(1) = (6)/(4)\cdot \alpha_(2) (From Eq. 2)


\alpha_(1) = (3)/(2)\cdot \alpha_(2)

Which means that polynomials
p_(1)(t) = 2\cdot t - 4\cdot t^(2) and
p_(2)(t) = 6\cdot t^(2)-3\cdot t are linearly dependent.

User SvenG
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.